TINGKAT KNOWLEDGE SHARING MAHASISWA DIUKUR DENGAN INSTRUMEN KNOWLEDGE SHARING BEHAVIOR SCALE - Wulan Romadhoni; Sri Sumaryati; Binti Muchsini (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2021)
ABSTRACT           The purpose of this study was to determine the level of knowledge sharing of students of Accounting Education at Sebelas Maret University. This research is a quantitative survey research with descriptive statistical data analysis techniques. The population in this study were all active students of the Sebelas Maret University Accounting Education Study Program in the 2018-2020 class, totaling 247 students. The sampling technique used is proportional random sampling with a sample of 149 students. The data collection technique used is a questionnaire. This study measures the level of knowledge sharing using the Knowledge Sharing Behavior Scale (KSBS) instrument from Yi (2009) with indicators of written contribution, organizational communication, personal interaction, and community practice. The conclusion of this study is that the level of knowledge sharing of students of Accounting Education at Sebelas Maret University can be categorized as poor. This refers to the TCR result of 63.49%. The implication of this research is that lecturers in the learning process can provide more support to all students and create a classroom atmosphere that supports knowledge sharing behavior. Students must also be aware of the importance of knowledge sharing behavior so that learning objectives can be achieved. Keywords: knowledge sharing level, KSBS, written contribution, organizational communication, personal interaction, community practiceABSTRAKTujuan penelitian ini untuk mengetahui tingkat knowledge sharing mahasiswa Pendidikan Akuntansi Universitas Sebelas Maret. Penelitian ini merupakan penelitian kuantitatif survei dengan teknik analisis data statistik deskriptif. Populasi dalam penelitian ini adalah seluruh mahasiswa aktif Program Studi Pendidikan Akuntansi Universitas Sebelas Maret angakatan tahun 2018-2020 yang berjumlah 247 mahasiswa. Teknik sampling yang digunakan adalah proportional random sampling dengan sampel sejumlah 149 mahasiswa. Teknik pengumpulan data yang digunakan adalah angket. Penelitian ini mengukur tingkat knowledge sharing menggunakan instrumen knowledge sharing behavior scale (KSBS) dari Yi (2009) dengan indikator kontribusi tertulis, komunikasi organisasi, interaksi pribadi, dan komunitas praktik. Kesimpulan penelitian ini adalah tingkat knowledge sharing mahasiswa Pendidikan Akuntansi Universitas Sebelas Maret, dapat dikategorikan kurang baik. Hal tersebut mengacu pada hasil TCR sebesar 63,49%. Implikasi dalam penelitian ini, dosen dalam proses pembelajaran dapat lebih memberikan dukungan kepada semua mahasiswa dan menciptakan suasana kelas yang mendukung perilaku knowledge sharing. Mahasiswa juga harus sadar mengenai pentingnya perilaku knowledge sharing agar tujuan pembelajaran dapat tercapai. Kata Kunci: tingkat knowledge sharing, KSBS, kontribusi tertulis, komunikasi organisasi, interaksi pribadi, komunitas praktik